Attributes, environment factors and women entrepreneurial activity: A literature review - Ekpe, Isidore; Mat, Norsiah; Che Razak, Razli (Canadian Center of Science and Education (CCSE), 2011)
Purpose: The purpose of this study is to examine the effect of individual attributes and business environment factors on the entrepreneurial activity of women entrepreneurs. Individual attributes such as education, working experience, attitude towards risk-taking, affect women entrepreneurial activity.Economic constraints such as lack of credit due to lack of asset collaterals and socio-cultural barriers, lack of savings due to low household income, and lack of labour skills due to low educational level also affect women entrepreneurial activity.The effect of these factors on entrepreneurial activity is worth studying because entrepreneurship development is considered a vital link to an overall economic growth of a nation through its positive impact on economic development especially at the grassroots.However, limited studies have reviewed literatures on individual attributes and business environment factors on the entrepreneurial activity of women entrepreneurs.This is the focus of this study. Methodology: The paper is a descriptive study that reviews literature on individual attributes and environment factors on women entrepreneurial activity. Conclusion: The paper concludes that environment factors exert much more influence on women entrepreneurial activity than individual attributes.Research limitation: The paper is limited to a literature review that may need further research by using a framework to investigate the factors on entrepreneurial activity.Practical implication: It shows the need for the government to support entrepreneurs through adequate provision of micro finance.Originality: The study is a new way to look at crucial factors affecting entrepreneurial activity in a country.Paper type: This is a research paper.